Detection of turkey coronavirus in commercial turkey poults in Brazil - Teixeira, Maria Cecilia B.; Luvizotto, Maria Cecilia R.; Ferrari, Heitor F.; Mendes, Analy R.; da Silva, Sergio E. L.; Cardoso, Tereza C. (Taylor & Francis Ltd, 2007)
Poult enteritis complex has been incriminated as a major cause of loss among turkey poults in other countries. We have observed this in Brazil, associated with diarrhoea, loss of weight gain and, commonly, high mortality In this study, we have used the reverse transcriptase polymerase chain reaction (RT-PCR) to detect turkey coronavirus (TCoV) in sick poults 30 to 120 days of age from a particular producer region in Brazil. The RT-PCR was applied to extracts of intestine tissue suspensions, and the respective intestinal contents, bursa of Fabricius, faecal droppings and cloacal swabs. Primers were used to amplify the conserved 3' untranslated region of the genome, and the nucleocapsid protein gene of TCoV Histo pathological and direct immunohistochemical examinations were performed to detect TCoV antigen in infected intestine and bursa slides. All the results from stained tissues revealed lesions as described previously for TCoV infection. The direct immunohistochemical positive signal was present in all intestine slides. However, all bursa of Fabricius tissues analysed were negative. RT-PCR findings were positive for TCoV in all faecal droppings samples, and in 27% of cloacal swabs. Finally, the best field material for TCoV diagnosis was faecal droppings and/or intestine suspensions.